Preventing and fighting stigma: a lesson from the first Mpox in Veneto region of Northeast Italy—A case report - Baldovin, Tatjana; Girolametto, Gloria; Geppini, Ruggero; Bordignon, Matteo; Alaibac, Mauro (Frontiers in Public Health, 2023)
Since the 1970s, human monkeypox (Mpox) has been referred to as a zoonotic endemic disease of specific regions of Africa until early 2022, when a worldwide epidemic outbreak developed. There are many hypotheses on how Mpox could spread to non-endemic regions; the dominant theory is that it spread from the UK and Spain among men who have sex with men (MSM). Therefore, the first clinical case in the Veneto region (Northeast of Italy) was analyzed—which represented a typical case report of the ongoing outbreak—with lesions located mainly in the areas associated with sexual behaviors (genital and oral). This case report highlights the new challenges of Mpox, as it seems to differ from the previous classic manifestation. Indeed, although the patient achieved restitution ad integrum of lesions and complete recovery from the disease, it is deemed necessary to offer communication strategies to involve a heterogeneous audience based on different risks of exposure but without stigmatizing attitudes, avoiding the mistakes made with HIV. The need for broad public involvement is demonstrated by identifying Mpox even in “anomalous cases.” Stigma could be an obstacle in engaging patients in proper care and in getting honest answers while contact tracing, as happened in our patient's case; thus, WHO recently renamed monkeypox as Mpox. Abnormal outbreaks in non-endemic countries, with no causal links, must become a warning signal for governments and health policies to design national plans for managing unexpected outbreaks. For an effective public health response, health institutions must communicate effectively, focus on changes and prevention measures, and formulate a plan based on equity and inclusion of the most vulnerable groups.